Zapożyczenia angielskie w polszczyźnie czasów pandemii COVID-19 - Piotrowicz-Krenc, Anna; Witaszek-Samborska, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The authors of the article look at the loanwords introduced into the Polish vocabulary during the COVID-19 pandemic. The division of these loans according to the mechanism of taking a lexeme or word combination over into the Polish language is based on the work of Alicja Witalisz. The material comes from online texts published between 2020 and 2023. Verification of the collected neologisms and collocations (over 1 570 lexical units) in English dictionaries and in The Coronavirus Corpus and Monco PL corpora (in both cases, taking into account the dates of the first record) allowed us to assume with high probability that 441 loanwords (proper loanwords, structural-semantic calques, semantic calques) appeared in Polish texts during the pandemic, reflecting the thematic nominative network of that period. It turned out that the fields powered by anglicisms are mainly: DISEASES AND THEIR TREATMENT, FUNCTIONING OF THE STATE and LAW AND LAW-BREAKING. English borrowings also occur in many other fields (e.g. LAW and LAW-BREAKING, HUMAN LIFE'S IMMEDIATE ENVIRONMENT, RULES OF SOCIAL COEXISTENCE, BUSINESS, FREE TIME or HUMAN MENTAL STATES).